Dynamics of organizational climate and job satisfaction in healthcare service practice and research: a protocol for a systematic review - Santana, Silvina; Pérez-Rico, Cristina (Frontiers in Psychology, 2023)
Organizational climate and job satisfaction have been established as fundamental pillars of research and practice in organizational behavior and organizational psychology, inspiring many explanations and operationalizations over time. In most sectors, global trends such as labor shortages, high rates of turnover and absenteeism, the need to increase productivity, and the interest in new work models concur to keep climate and job satisfaction on top of the research agenda. The situation is particularly acute in the healthcare sector, where related factors have the capacity to influence all aspects of care provision, including patient safety and the physical and mental health of care providers. Nevertheless, a gap in knowledge persists regarding climate, job satisfaction, and their relationships in healthcare services. This protocol describes a study that aims to examine the dynamics of climate and job satisfaction in healthcare organizations from the practice and research perspectives. The protocol complies with PRISMA-P. PRISMA will be used to report the results of the study. Databases will be searched for published studies in May 2023, and we expect to complete the study by December 2024. A framework based on a multi-dimensional concept of quality in research will be used to examine the quality of any studies before inclusion. The results will be disseminated in two systematic reviews. We will describe proposed models depicting the dynamics of climate and job satisfaction in healthcare organizations. We will systematize and discuss available evidence regarding the outcomes of climate and job satisfaction in healthcare work environments. We will synthesize information on research designs and methodological options of included studies. We will identify measures of climate and job satisfaction used in healthcare settings, assess their psychometric properties, and appraise the overall quality of underlying studies. Finally, we expect to identify areas in need of further research.